Rancang Bangun Stasiun Pengisian Daya Listrik Berbasis Panel Surya dengan Variasi Profil Pada Penopang Panel Surya - Aji Saputra; Ade Sunardi; Mohamad Zaenudin (Integrated Mechanical Engineering Journal, 2023)
Solar panel-based electric charging stations are a combination of electricity sources and solar panels, allowing efficient and effective charging and helping to source electricity from natural energy in the form of renewable energy, namely the sun. The use of solar panels as the main energy source can reduce dependence on limited energy sources and produce lower greenhouse gas emissions and reduce dependence on fossil energy sources. The purpose of this thesis is to design and analyze the strength and durability of solar panel-based electric charging stations on their supports. The method used in this study is quantitative data taken using Ansys software simulations. The results showed that Design 1 on the solar panel supports had a maximum deformation of 0.2397 mm at an angle of 70 and design 2 produced a maximum deformation of 0.0052439 mm at an angle of 70 to the right/left. Based on these results, it can be concluded that the design of 1 solar panel support is better in terms of strength and durability because the load on the solar panel that is on the support only has an effect of 0.2397 mm which can withstand a load of around 320 N.